Recent advances in CE-MS coupling: Instrumentation, methodology, and applications - Týčová, Anna; Ledvina, Vojtěch; Klepárník, Karel (Electrophoresis, 2017)
This review focuses on the latest development of microseparation electromigration methods in capillaries and microfluidic devices coupled with MS for detection and identification of important analytes. It is a continuation of the review article on the same topic by Kleparnik (Electrophoresis 2015, 36, 159-178). A wide selection of 161 relevant articles covers the literature published from June 2014 till May 2016. New improvements in the instrumentation and methodology of MS interfaced with capillary or microfluidic versions of zone electrophoresis, isotachophoresis, and isoelectric focusing are described in detail. The most frequently implemented MS ionization methods include electrospray ionization, matrix-assisted desorption/ionization and inductively coupled plasma ionization. Although the main attention is paid to the development of instrumentation and methodology, representative examples illustrate also applications in the proteomics, glycomics, metabolomics, biomarker research, forensics, pharmacology, food analysis, and single-cell analysis. The combinations of MS with capillary versions of electrochromatography, and micellar electrokinetic chromatography are not included.
Keywords: Cell Line; isoelektrická fokusace; metabolomika; Metabolomics; CE; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Single-Cell Analysis; MS; Mass Spectrometry; glykomika; elektroforéza kapilární; Electrospray; Spectrometry, Mass, Electrospray Ionization; analýza potravin; Microfluidic devices; laboratoř na čipu; Humans; biologické markery; Food Analysis; chromatografie; Isoelectric Focusing; analýza jednotlivých buněk; spektrometrie hmotnostní - ionizace laserem za účasti matrice; buněčné linie; Lab-On-A-Chip Devices; Chromatography; Electrophoresis, Capillary; Biomarkers; hmotnostní spektrometrie s elektrosprejovou ionizací; Glycomics; hmotnostní spektrometrie; lidé